ANALISIS IMPLEMENTASI GOOD GOVERNANCE DALAM PELAYANAN PUBLIK DI KECAMATAN MALUNDA KABUPATEN MAJENE - Sri Wulan; Abd. Asis (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2018)
This study aims to determine the implementation of the concept of good governance public services Malunda District Government. This can be seen in the District Government Performance Accountability Report. The duties and functions of the Malunda District Government apparatus are based on the Majene Regency Government Regulation on the main duties of the function and job descriptions. The implementation of the duties and functions of the Malunda District Government apparatus involving public and private participation can be seen through participation in the field of hygiene and environment, community development and empowerment, services, and provision of goods to sub-district government officials in supporting government administration activities.